2014
DOI: 10.1371/journal.pone.0103605
|View full text |Cite
|
Sign up to set email alerts
|

Wavefront-Guided versus Non-Wavefront-Guided Photorefractive Keratectomy for Myopia: Meta-Analysis of Randomized Controlled Trials

Abstract: PurposeTo compare the efficacy, predictability, safety, and induced higher-order aberrations (HOAs) between wavefront-guided and non-wavefront-guided photorefractive keratectomy (PRK).MethodsThe Cochrane Central Register of Controlled Trials, PubMED, and EMBASE were searched for randomized controlled trials. Trials meeting the selection criteria were quality appraised, and data was extracted by 2 independent authors. Measures of association were pooled quantitatively using meta-analytical methods. Comparisons … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…There is some controversy regarding the relationship between human eye HOAs and myopia diopter. Some studies [ 23 , 24 ] showed more positive HOAs in higher diopter myopia, whereas other studies [ 25 , 26 ] showed less positive HOAs in higher diopter myopia. Moreover, other research studies [ 8 , 25 ] showed no relationship between HOAs and myopia diopter.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some controversy regarding the relationship between human eye HOAs and myopia diopter. Some studies [ 23 , 24 ] showed more positive HOAs in higher diopter myopia, whereas other studies [ 25 , 26 ] showed less positive HOAs in higher diopter myopia. Moreover, other research studies [ 8 , 25 ] showed no relationship between HOAs and myopia diopter.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies [ 23 , 24 ] showed more positive HOAs in higher diopter myopia, whereas other studies [ 25 , 26 ] showed less positive HOAs in higher diopter myopia. Moreover, other research studies [ 8 , 25 ] showed no relationship between HOAs and myopia diopter. Our study focused on cornea HOAs and mild to moderate myopic eyes in adolescents.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 4 To decrease the aberrations and improve the visual quality, today several customized cutting pattern are performed. 5 - 7 Unfortunately still there is no perfect effect about the corneal refractive surgery. In this present study we observed the corneal aberrations and visual functions of myopic patients after LASIK guided by aspherical ablation with 4-year follow-up to explore their long-term stability.…”
Section: Introductionmentioning
confidence: 99%